2020
DOI: 10.1111/asj.13426
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between circulating leptin concentrations and growth performance, carcass traits, and meat quality indexes in finishing Simmental × Luxi bulls fed high‐concentrate diets

Abstract: Leptin is a hormone produced by adipocytes that has been shown to have a wide range of biological actions in cattle (Wylie, 2011), and it is considered a potential indicator to evaluate and select animals for a certain production setting or as a potential indicator trait in genomic prediction programs (Foote et al., 2015; Foote, Tait, Keisler, Hales, & Freetly, 2016). Until now, there are a few relevant literatures for association of leptin concentrations with production traits in beef cattle, and as a corrobo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…It is reported that high‐concentrate diets can bring some positive changes in milk yield, milk composition, and milk fatty acid content of dairy cows and dairy goats (Dong et al, 2017; Magan et al, 2021). On the other hand, it is worth noting that high‐concentrate diets also play a role in the growth performance, carcass traits, and meat quality of ruminants (Da et al, 2015; Geng et al, 2020; Majdoub‐Mathlouthi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that high‐concentrate diets can bring some positive changes in milk yield, milk composition, and milk fatty acid content of dairy cows and dairy goats (Dong et al, 2017; Magan et al, 2021). On the other hand, it is worth noting that high‐concentrate diets also play a role in the growth performance, carcass traits, and meat quality of ruminants (Da et al, 2015; Geng et al, 2020; Majdoub‐Mathlouthi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some SNPs in LEP promoter have been shown to alter plasma LEP level and to influence fertility, energy balance, and milk protein yield of Holstein‐Friesian cattle (Liefers et al, 2005). Geng et al (2020) also reported the association between LEP concentration and several quality traits including marbling of Simmental × Luxi F1 crossbred cattle, although their analysis did not show the effects on meat tenderness and juiciness. To apply these SNPs as a DNA marker, detailed association study with bigger population and expression analysis will be required.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin is a hormone synthesized and secreted from adipocytes and plays a crucial role in biological functions in cattle. Leptin concentration is positively correlated with meat thickness, marbling score, and intramuscular fat, and is also negatively correlated with cholesterol content [112][113][114]. This indicates supplementation of leptin in meat culture media gives us promising results and improves the meat yield and quality.…”
Section: Potential Application Of Serum Markers For Culture Meat Prod...mentioning
confidence: 94%